1996
DOI: 10.4315/0362-028x-59.9.932
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Culture Filtrate from Heat-Injured and Repaired Listeria Strains: Assay on Bovine Mammary Epithelial (MAC-T) Cells

Abstract: The cytotoxic effect of culture filtrates from healthy, heat-stressed, and repaired Listeria monocytogenes and L. innocua on the bovine mammary epithelial cell line MAC-T was examined. Culture filtrates were collected from Listeria spp. following treatments which included: (i) 18 h of growth of Listeria at 37°C; (ii) sublethal heat treatment at 56°C for 50 minutes; (iii) repair of the injured cells at 37°C for 7 h; (iv) growth of repaired bacterial cells at 37°C for 36 h; and (v) heat injury at 56°C for 50 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Cytotoxicity assays conducted by previous researchers did not include many L. ivanovii strains in their test panel (Del Corral et al 1990 ;Bunduki et al 1996 ;Dallas et al 1996). In this study, it was found that six strains of L. ivanovii had some cytotoxic effect (as indicated by AP release) on Ped-2E9 cells and five strains had a significantly lower cytotoxic effect than L. monocytogenes strains (Fig.…”
Section: ------------------------------------------------------------mentioning
confidence: 69%
See 1 more Smart Citation
“…Cytotoxicity assays conducted by previous researchers did not include many L. ivanovii strains in their test panel (Del Corral et al 1990 ;Bunduki et al 1996 ;Dallas et al 1996). In this study, it was found that six strains of L. ivanovii had some cytotoxic effect (as indicated by AP release) on Ped-2E9 cells and five strains had a significantly lower cytotoxic effect than L. monocytogenes strains (Fig.…”
Section: ------------------------------------------------------------mentioning
confidence: 69%
“…Rapid detection as well as pathogenicity testing of this organism is essential for controlling incidence of listeriosis. Various mammalian cell lines have been tested for their efficacy to determine virulence of L. monocytogenes in vitro, including intestinal cells (Del Corral et al 1990 ;Pine et al 1991 ;Schlech et al 1994 ;Bunduki et al 1996), fibroblasts (Siddique 1969), and macrophage cells (Portnoy et al 1988 ;Dallas et al 1996). In these cell lines, cytotoxicity was determined by the invasion assay or the trypan blue exclusion test, or by observing morphological changes.…”
Section: Introductionmentioning
confidence: 99%
“…Both soil and glass are substrates to which pathogenic and non-pathogenic Listeria strains frequently attach to in nature(Astwood and Wais 1998; Allan, Yan et al 2004) and during food processing(Thomas, King et al 1991; Hutter and Bechhoefer 1993). The force constant of each cantilever was determined prior to force measurements from the power spectral density of the thermal noise fluctuations in DI water(Bunduki, Zavizion et al 1996; Ayebah, Hung et al 2005). Force measurements were performed under water since water is considered as the main solvent in many in vitro environments such as those used in food-related industries where Listeria cells contaminate inert surfaces(Karunasagar, Krohne et al 1993; Lahellec, Salvat et al 1996; Engelbrecht, Dominguez-Bernal et al 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Since E. coli has a teichoic acidlike O-polysaccharide in its surface structure in spite of being a gram-negative bacterium (Perepelov et al 2006) , chlorine stress and fungicide stress may have been more effective in sublethally injuring E. coli and E. coli able environment. In addition, many injured pathogens either retain or exhibit enhanced virulence after resuscitation (McCarthy 1991;Hernández et al 1993;Bunduki et al 1996;Rowe and Kirk 2000) . Therefore, the rejuvenation of injured bacteria can increase the risk of underestimating the microbiological quality and safety of fresh produce from the farm to the table.…”
Section: Sublethally Injured Bacteria During Production Of Vegetablesmentioning
confidence: 99%